Answer :
You have the following expression:
9x² - 12x + 4
In order to factorize the previous expression, use the quadratic formula, given by:
[tex]x=\frac{-b\pm\sqrt[]{b^{2}-4ac}}{2a}[/tex]where a, b and c are the coefficients of the polynomial.
In this case, you have:
a = 9
b = -12
c = 4
replace the previous values of the parameters into the quadratic formula:
[tex]\begin{gathered} x=\frac{-(-12)\pm\sqrt[]{(-12)^{2}-4(9)(4)}}{2(9)} \\ x=\frac{12\pm\sqrt[]{144-144}}{18} \\ x=\frac{12}{18}=\frac{2}{3} \end{gathered}[/tex]Hence, the factor of the given polynomial is:
(x - 2/3)(x-2/3)